On the mechanics of fiscal inflations - Marco Bassetto; Luca Benzoni; Jason Hall (Federal Reserve Bank of Chicago, 2024)
The goal of this paper is twofold. First, we wish to better explain the relationship between Sargent and Wallace's (1981) unpleasant monetarist arithmetic, the closely connected fiscal theory of the price level (FTPL), and the monetarist view of inflation. Second, we discuss how the recent inflationary episode has contributed to redistributing real resources from holders of government debt to the public purse. In particular, financial prices before the onset of the Covid pandemic suggest that investors viewed an inflationary shock such as the one we experienced as extremely unlikely, so the magnitude of this redistribution caught them by surprise.
Keywords: 330; fiscal theory of the price level; FTPL; unpleasant monetarist arithmetic; monetarism; Redistribution effect of inflation; Fiscal Inflation; Price Level; Inflation; Deflation; Money Supply; Credit; Money Multipliers; Fiscal Policy; General Financial Markets; General (includes Measurement and Data); Macroeconomics and monetary economics; Financial Economics